The In Vitro Efficacy of Antimicrobial Agents Against the Pathogenic Free‐Living Amoeba Balamuthia mandrillaris. (19th July 2013) - Ahmad, Arine F.; Heaselgrave, Wayne; Andrew, Peter W.; Kilvington, Simon
Abstract: The free‐living amoeba Balamuthia mandrillaris causes usually fatal encephalitis in humans and animals. Only limited studies have investigated the efficacy of antimicrobial agents against the organism. Assay methods were developed to assess antimicrobial efficacy against both the trophozoite and cyst stage of B. mandrillaris (ATCC 50209). Amphotericin B, ciclopirox olamine, miltefosine, natamycin, paromomycin, pentamidine isethionate, protriptyline, spiramycin, sulconazole and telithromycin had limited activity with amoebacidal levels of > 135–500 μM. However, diminazene aceturate (Berenil ® ) was amoebacidal at 7.8 μM and 31.3–61.5 μM for trophozoites and cysts, respectively. Assays for antimicrobial testing may improve the prognosis for infection and aid in the development of primary selective culture isolation media.